PENGARUH SUHU PENGERINGAN OVEN TERHADAP AKTIVITAS ANTIOKSIDAN BUBUK DAUN CEMCEM (Spondias pinnata (L.f) Kurz) - Willigis Benito Khatulistiwa, I Putu; Mayun Permana, I Dewa Gde; Puspawati, I Gusti Ayu Kadek (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 9 No 3 (2020): Jurnal ITEPADO - 10.24843/itepa.2020.v09.i03.p11, 2020)
This study aimed to determine the effect of oven drying temperature on the antioxidant activity of cemcem leaf powder and get the rightest oven drying temperature to produce cemcem leaf powder which had the highest antioxidant activity. The experimental design used was a completely randomized design with a drying temperature treatment consisting of consisting of 4 levels including: 40oC, 50oC, 60oC and 70oC. The treatment was repeated 4 times to obtain 16 experimental units. The data obtained were analyzed using variance analysis, if it had a significant effect then it was continued with the Duncan Multiple Range Test (DMRT). The results showed the drying temperature had a very significant effect (p<0.01) on water content, total phenolic, total flavonoids and antioxidant activity. Drying temperature of 50oC is the best temperature to produce cemcem leaf powder with the highest antioxidant activity of 61.98% with IC50 79.58 ppm, total phenolic 48.03 mg GAE/g powder, total flavonoids 49.11 mg QE/g powder, water content 7.78%.